Brain network functional connectivity changes following psychosocial stress in subjective cognitive decline: Neuropsychiatry and behavioral neurology/presymptomatic disease/prodromal disease/prodromal states. (7th December 2020) - Albert, Kimberly; Boyd, Brian; Newhouse, Paul A.; Taylor, Warren D.
Abstract: Background: Neurodegenerative processes in early AD may disrupt the coordinated activity of brain networks important for the regulation of endocrine and emotional stress response. Stress reactivity and the effect of psychosocial stress on brain network function may thus be useful markers of neural changes related to early AD processes. The goal of this study was to examine the effect of psychosocial stress on brain network function in older adults with Subjective Cognitive Decline (SCD), a population at increased risk for Alzheimer's disease. Method: Participants (n=25) were evaluated to exclude cognitive impairment and significant psychiatric disorders. SCD was operationalized using the Cognitive Complaints Index (CCI) with a required minimum score of 20%. The Montreal Imaging Stress Task (MIST) was used to induce moderate psychosocial stress. Subjective measures included the stress subscale of the Stress‐Arousal Checklist (SACL) and the Profile of Mood States (POMS). Resting‐state fMRI scans were completed before and after the MIST. Seed‐based analyses were used to examine changes in functional connectivity (FC) in the default mode (DMN‐posterior cingulate), cognitive control (CCN‐dorsolateral prefrontal cortex), and salience (SN‐anterior insula) networks (p uncorrected <0.005, FDR corrected p <0.05). Result: Participants had an average CCI of 45% (SD = 10.5%). There was an increase in subjective stress (stress‐SACL; t=6.12, p < 0.0001) and worsening mood symptoms (POMS total score; t=3.23, p=0.004) during the MIST. In the DMN, stress exposure with the MIST resulted in decreased FC between the posterior cingulate cortex and regions of the CCN, (middle and superior frontal gyri). In the SN, stress exposure increased FC between the right anterior insula and the right middle/inferior temporal gyri and DMN regions including the precuneus and posterior cingulate cortex. We did not observe changes in FC in the CCN. Conclusion: These findings suggest that in SCD stress reduces coordinated activity of the CCN and DMN and increases connectivity between SN and DMN which may reflect impaired regulation of DMN activity and enhanced vigilance for emotional information. Further work is needed to determine how these changes may differ from normal aging and whether network changes may indicate early AD‐related cognitive and emotional disruption.